Characterization of the mass transfer of lyophilized products based on X-ray micro-computed tomography images. Issue 8 (11th June 2017) - Pisano, Roberto; Barresi, Antonello A.; Capozzi, Luigi C.; Novajra, Giorgia; Oddone, Irene; Vitale-Brovarone, Chiara
ABSTRACT: This paper proposes a systematic work process for the rapid determination of resistance to vapor flow given by the products being freeze-dried. This approach couples mathematical modeling and 3D nondestructive X-ray imaging to reconstruct the internal structure of lyophilized samples. Knowledge of the internal structure is fundamental to better understand the relationship between freezing and within-product heterogeneity as well as between freezing and the drying behavior of the product being lyophilized. The method was validated upon mannitol-based formulations using various freezing protocols. This stepwise approach was demonstrated to be helpful to lyophilization professionals for the control of within-product heterogeneity and for the optimization of the cycle.